2019
DOI: 10.1590/0001-3765201820180232
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicology assay for the evaluation of environmental water quality in a tropical urban estuary

Abstract: Most studies evaluating the impacts of river pollution in the semi-arid region of Brazil have been geared towards physiochemical analyses, and investigations of the adverse effects of water pollution on associated organisms are scarce. This study aimed to evaluate the water quality in the Poxim river estuary in Aracaju, Sergipe throughout the dry and rainy season by evaluating the survival of the microcrustacean Mysidopsis juniae and physicochemical analyses. The evaluation of physiochemical parameters reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
(21 reference statements)
1
11
0
2
Order By: Relevance
“…On the other hand, the decanter sludge showed to be highly toxic, with LOEC of 20% and 15% in collections 4 and 5, respectively (Figure 3). Studies in the Poxim estuarine region have already identified low environmental quality for both water and sediment samples [33], and WTP Poxim effluents may be contributing to the environmental degradation of this estuary.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the decanter sludge showed to be highly toxic, with LOEC of 20% and 15% in collections 4 and 5, respectively (Figure 3). Studies in the Poxim estuarine region have already identified low environmental quality for both water and sediment samples [33], and WTP Poxim effluents may be contributing to the environmental degradation of this estuary.…”
Section: Resultsmentioning
confidence: 99%
“…No entanto, não se pode desprezar as matrizes ambientais água e sedimento, pois estas trazem informações relevantes para entender o ambiente, através da detecção de marcadores moleculares. A cidade de Aracaju, por exemplo, apresenta uma significativa concentração populacional na zona costeira (Nilin et al, 2019). No entanto, pouco se sabe sobre as atuais condições de saúde de estuários localizados nesta cidade e, no sistema estuarino Sergipe-Poxim, a distribuição de marcadores moleculares é pouco conhecida.…”
Section: Capítulo 10unclassified
“…Poxim é um bom exemplo para entender a relação entre as atividades humanas e suas influências no ecossistema. Localizado no Nordeste do Brasil, este ambiente aquático é um dos principais sistemas estuarinos do estado de Sergipe e uma importante fonte econômica para a cidade de Aracaju(Souza et al, 2018;Nilin et al, 2019). Não obstante, as atividades antropogênicas podem representar forte influência na dinâmica fluvial deste ambiente.…”
unclassified
“…Some animals, especially invertebrates, are being used as experimental models to assess the effects of anthropogenic discharge on aquatic ecosystems (Silva et al 2017, Nilin et al 2019. Among them, marine crustaceans have been studied to assess the impact of chemicals in estuarine and marine environments (Figueirêdo et al 2015), as these compartments can become a final sink of effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Mysidopsis juniae (Mysidacea) is a species of microcrustacean that is important in trophic chains as it feeds on phytoplankton and other microcrustaceans (Domingues & Bertoletti 2006) and is a food source for several fish species. This species has been used in ecotoxicological tests because of its ecological importance to the structure of the aquatic food web and its higher sensitivity to a wide range of xenobiotics than other test organisms (Verslycke et al 2004, Bif et al 2013, Gurgel et al 2016, Silva et al 2017, Nilin et al 2019. In Brazil, the Brazilian Association of Technical Standards has standardized an acute toxicity test for M. juniae (ABNT 2011) and other studies have indicated that this species is a good candidate for chronic toxicity testing (Figueirêdo et al 2016).…”
Section: Introductionmentioning
confidence: 99%